Mobility investigation of an intelligent air-cushion tracked vehicle on swamp peat terrain in Malaysia - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (SAE International, 2011)
This study presents the vehicle mobility in terms of traction mechanics for the developed small scale intelligent aircushion tracked vehicle (IACTV) moving over swamp peat.The air cushion system partially supports the 20 % of vehicle total weight in order to make the vehicle ground contact pressure 7 kN/m2. As the air-cushion support system can adjust automatically on the terrain, so the vehicle can move over the terrain without any risks. The spring-damper system is used with the vehicle body to control the air-cushion support system on any undulating terrain by making the system sinusoidal form but an unstable heave motion is developed under these conditions. The experiment and simulated performance results such as tractive efficiency of 60-72 % and corresponding traction coefficient of 50-55 % for the vehicle slippage of 3-10 % indicate that the developed vehicle can meet the swamp peat terrain requirement with its optimal power consumption.